The Opportunity of the Waste Bank as One of the Livelihoods for the Community - Puspitasari, Yanti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
If we want to try, there are many ways you can do, in terms of entrepreneurship, for example, there are waste bank activities. For some people, managing waste is an activity that is underestimated, an activity that has little economic value and is a profession for the lower classes. However, recently the concept of a waste bank has been able to ward off this negative stigma, as it has been proven that many waste business actors have made huge profits. This is proof, whatever the form of business and profession, if done properly and correctly, can provide maximum benefits. This study was conducted to analyze the activities of the waste bank, so that the potential economic value is known. This research is qualitative with descriptive analysis, in which the exploration of phenomena is done naturally. The object of this research is the waste bank group in Pamulang, South Tangerang. The research data were obtained through in-depth interviews, discussions, observations, and documentation. The results obtained information, that the waste management business is an activity that has economic value. As for the size of the economic value, it really depends on skills in managing waste and marketing it to the community. Thus it can be said that in waste bank activities there are opportunities or economic value obtained, but expertise in managing waste and the ability to sell processed products are the determining factors, how these opportunities can become one of the community entrepreneurial activities.